If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + 3 + -1b = -7 + 2 + b Reorder the terms: 3 + 4b + -1b = -7 + 2 + b Combine like terms: 4b + -1b = 3b 3 + 3b = -7 + 2 + b Combine like terms: -7 + 2 = -5 3 + 3b = -5 + b Solving 3 + 3b = -5 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 3 + 3b + -1b = -5 + b + -1b Combine like terms: 3b + -1b = 2b 3 + 2b = -5 + b + -1b Combine like terms: b + -1b = 0 3 + 2b = -5 + 0 3 + 2b = -5 Add '-3' to each side of the equation. 3 + -3 + 2b = -5 + -3 Combine like terms: 3 + -3 = 0 0 + 2b = -5 + -3 2b = -5 + -3 Combine like terms: -5 + -3 = -8 2b = -8 Divide each side by '2'. b = -4 Simplifying b = -4
| 6-3(4x+2)-10x= | | (-X+1)2+(-x-1)2=0 | | k+12/17=2 | | 8x+3=8x+3-4x+29 | | 80x^4-48x^2+4=0 | | 16-2(x-5)= | | -21x+5=-40 | | 11x+13=108 | | half(7x-2)+5=2x+7 | | 3a^2-8a+4=0 | | 3x+8=2x+1 | | 8x-5=8(x+6) | | -7n-3(n+7)=3-6n | | -72-3(n+7)=3-6n | | 7+(-3)v=6+v | | y=hx+f | | 3x^3+14x^2-12x=0 | | 9c+5-6=9 | | 5x^3-3x-2=0 | | 16x=12x+52 | | X-1=2y | | a^3b^5x=a^7b^5c^3 | | 3y^5*6y= | | 12x(x+1)=42(x+1)-(3x-42) | | 4.5=-3(-2.5)+b | | 2n-14=-8(7+5n) | | 2n-1=-8(7+5n) | | 3.14r^2=5 | | 3(3.5x+3.75)=3(4.75x+4) | | 6x-2=3x-44 | | 9e-5=22 | | 6x-1=2x-93 |